Pengaruh Model Problem Based Learning Dan Discovery Learning Terhadap Kemampuan Pemecahan Masalah Siswa - Bettri Yustinaningrum; Aida Fitri; Juliana (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to compare the mean problem-solving ability of students treated with the problem-based learning with discovery learning on the SPLDV material. The population in this study were all students of class VIII SMPN 4 Takengon. Sampling using cluster random sampling selected classes VIII2 and VIII3. Data collection techniques using tests and observations. The research instrument used a problem-solving ability test and observation sheet. The data analysis technique uses the t-test which is used to compare problem-based learning with discovery learning. Based on the research results, it was found that the mean problem-solving ability treated with the problem-based learning model was higher than that given the discovery learning treatment. The difference in the mean problem-solving ability between the problem-based learning and discovery learning classes is caused by the different treatment given to the two classes.